METODE OUTDOOR LEARNING DI SEKOLAH DASAR\ - Sissy Suhadayanti; Harlinda Syofyan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Learning in elementary schools generally still focuses on classroom activities using monotonous lecture methods. This condition makes students less motivated and difficult to connect theory with real experiences. Therefore, alternative learning methods that are contextual, interactive, and fun are needed. One relevant approach is outdoor learning, which is learning activities outside the classroom that utilize the environment as a learning resource. Gardening was chosen as the medium because it integrates cognitive, affective, and psychomotor aspects while fostering environmental awareness. The purpose of this study was to describe the application of the outdoor learning method in gardening activities and to identify its impact on the development of elementary school students at PKBM Tunas Bangsa. The research used a descriptive qualitative approach with research subjects consisting of 1 tutor and 4 students aged 9–11 years. Data was collected through observation, interviews, and documentation. Data analysis used the Miles & Huberman model, which includes data reduction, data presentation, and conclusion drawing, and data validity was strengthened by triangulation of sources and techniques. The results of the study show that gardening activities with an outdoor learning approach make students more enthusiastic, active, and able to connect theory with real practice. This activity improves understanding of science and the environment, develops motor skills, and fosters positive character traits such as responsibility, discipline, cooperation, and concern for the environment. Thus, the outdoor learning method has proven to be an effective alternative learning strategy for elementary school students, both in formal and non-formal education contexts.